PENGARUH IKLIM ORGANISASI DAN BEBAN KERJA TERHADAP MORAL KERJA KARYAWAN DI PT. STUDIAN TATA DINAMIKA DI PEKANBARU - Firmansyah Putra; Jumiati Sasmita; Nuryanti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research held in PT. Studian Tata Dinamika Pekanbaru. This research held in order to analyze the influence of organizational climate and workload to employees’ work morale. Population are all employees, consist of 44 people which was using cencus sampling model. Variables used are organizational climate and workload as independent and work morale as dependent. Data analyzed by using descriptive and multiple regression analysis by using SPSS 19 for windows. Result of this study shows that both organizational climate and workload significantly influence simultenously to employees’ work morale. Partially, organizational climate positively and significantly effect to work morale. While, workload negatively but not significantly effect to employees’ work morale. It is recommended to company to enhance the organizational climate conducievity by providing awardness program and definite a clear and measureable achievement parameter to all employees. Workload analysis need to be done proportionally and recreational activities also need to be held to decline the negative side effect of workload to employees.Keywords: Organizational Climate, Workload and Work Morale